Določanje kratkoročnih sprememb na klifu med Fieso in Pacugom s podatki letalskega lidarja - Kolega, Nataša (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2016)
The paper deals with the problem of determining short-term changes in the flysch cliffs on Slovenian coast using two datasets of airborn lidar scannings, with an interval of three years. Method has still been developing, it is usually combined primarily with terrestrial lidar. In the case study area of the cliff between Fiesa and Pacug (Slovenia) we undertook experimental test: most of the changes occurred on the wall of the cliff and on abrasion platform, on the central part of the cliff. We can conclude that this is the most active part of the cliff. Despite several deficiencies, the method has proven to be useful and relatively reliable.
Keywords: erozija; fliš; geomorfologija; geomorphology; klifi; morske obale; relief; Slovenia; Slovenija; topography